African honeybees as a mitigation method for elephant impact on trees. (January 2018) - Cook, R.M.; Parrini, F.; King, L.E.; Witkowski, E.T.F.; Henley, M.D.
Abstract: Conservation managers are concerned about the impact that African elephants ( Loxodonta africana ) have on large tree species, necessitating the need for mitigation methods. Elephants actively avoid contact with African honeybees ( Apis mellifera subsp. scutellata ), staying clear of crop fields surrounded by beehive fence-lines and moving away from the sounds of swarming honeybees. Therefore, our objectives were to test whether the presence of beehives in trees influenced the likelihood of the tree receiving elephant impact, and compare these results to wire-netted (method used to prevent bark-stripping) and control (no treatment) trees. We selected a tree highly sought after by elephant, the marula tree ( Sclerocarya birrea subsp. caffra ), as our study species. We also assessed whether elephants avoided areas with marula trees containing beehives. Finally we provide a comparison of the financial costs of the beehive and wire-netting mitigation methods. We hung 50 active beehives in 50 trees, with 50 dummy beehives hung from branches on the opposite ends of each tree's main stem. We wire-netted another 50 trees and then assigned 50 trees as a control. Elephant impact on all 150 trees was measured prior to the addition of treatments and then post-treatment addition for 9 months. 54% of the control trees received some form of elephant impact, in comparison to 28% of the wire-netted trees and only 2% of the beehive trees. Wire-netting protected trees against bark-stripping but did not prevent elephants from breaking branches. Beehives proved to be the more effective mitigation method for elephant impact on large trees, although the presence of beehives did not prevent elephants from moving through the study site. The financial cost and maintenance required for the beehive mitigation method are greater than that of wire-netting, but the beehives can provide honey as an additive benefit on a small-scale usage level. Graphical abstract: Image 1 Highlights: Only 2% of trees with beehives received elephant impact. Beehives were more effective than wire-netting at protecting trees from impact. Beehives are more expensive than wire-netting, and require greater maintenance. Beehives provide an alternative method for protecting large trees from elephants.